Uporabniki, izposoja in postavitev knjižnične zbirke v splošni knjižnici Bežigrad - Kobal, Marija (Knjižnica, 2010)
A public library is aimed to provide services to all age groups of a community. Thus, it should attempt to meet the specific needs of each user age group. The article is based on the empirical analysis of statistical data of the Bežigrad Public Library for the year 2007, a year before the integration of all Ljubljana public libraries and the merge of membership database took place. The lending of library collection arranged by the potential user age groups was analysed and consequently the suitability of shelf arrangement was evaluated. The results showed the circulation of users in the individual library departments when borrowing fiction or non-fiction.
Keywords: splošne knjižnice; Knjižnica Bežigrad; postavitev gradiva; izposoja; uporabniki